Acetylated DNA-damaging clerodane diterpenes from Casearia sylvestris - de Carvalho, PRF; Furlan, Maysa [UNESP]; Young, MCM; Kingston, DGI; Bolzani, Vanderlan da Silva [UNESP] (Elsevier B.V., 1998)
In addition to the known diterpene casearin G (1), two new clerodane diterpene casearins type, casearin S (2) and casearin T (3), were isolated from an acetylated bioactive CH2Cl2/MeOH extract from leaves of Casealia sylvestris. The diterpenes 1-3 exhibited moderate but selective activity towards the DNA-repair deficient yeast Saccharomyces cerevisiae mutants RAD 52YK and RS 321. The structures of 1-3 were established on the basis of NMR spectroscopic experiments (C) 1998 Elsevier B.V. Ltd. All rights reserved.
Keywords: Casearia sylvestris; flacourtiaceae; diterpene; clerodane; casearins; DNA-damaging activity